Kitabistic Development in Vilnius University - Мишкинене, Галина (Slavistica Vilnensis, 2009)
In XVI century, when mothertongue was lost, Lithuanian Tatars started translate their religion books into old Belarusian, and later into Polish languages. This is how Tatars Slavonic writing in Arabic scripts appeared. The very first scientist who described Lithuanian Tatars’ manuscript in 1838 was German orientalist H.O. Fleischer. But the main discoverer of this writing is considered A. Muchlinski. In Vilnius University research of these manuscripts was started in 1960s’ by Professor A.K. Antonovich. His monograph ‘Бeлoрyсскиe тексты, писанные арабским писмом, и их графико-орфографическая система’ (Vilnius, 1968) became the main course book for further researchers. His research was followed by Professor V.N. Chekmonas, who was kitabistic school father in Vilnius University. Vilnius kitabistic school gives attention to manuscripts transliteration problems, its’ catalog formation, publication of sources and textual analysis.